(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In the article, we researched dynamic series of product cost using the reporting data of the NE «LRP “Motor”. We suggest applying econometric modelling inasmuch as it can help conduct the complex analysis not only in short periods, but also in the large scope dynamics. In our opinion,implementing this method will give an opportunity to make effective trend forecasts and thus, provide accurate analytical maintenance for the enterprise in the field of product costing. Article has both scientific and high practical value.